Peran Kepala Sekolah dalam Supervisi Pendidikan - Nurkholis Nurkholis; Muhammad Anang Fauzi; Azizah Mega Yulianti; Dwi Lestari; Pangesti Wahyuning Mulia (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
This paper aims to explain the role of principals in educational supervision. The principal has a role in quality development, school progress, improvement, approaches to learning methods and techniques, curriculum development, and creating a conducive and integrative learning climate. Educational supervision is currently developing very rapidly, thus encouraging the acceleration of science and information technology growth. Therefore, education must improve the quality of learning in schools. Schools as formal educational institutions must develop all the potential possessed by students. This research is library research with data sources in books or manuscripts related to school principals' leadership and educational supervision. This research is library research with data sources in manuscripts or books containing leadership principals in academic management. This research uses documentation data collection techniques and inductive data analysis. These findings indicate that the principal's leadership in educational supervision plays a central role in building school organizations to realize quality education.